Effect of Surface Imperfections on the Thermocouple Performance - Noerpamoengkas, Ardi; Ismail, Ahmad Yusuf; Mahamudin, Muhammad Fauzan (Journal of Advanced Research in Applied Mechanics, 2020)
Thermocouple is one of the most widely used temperature sensor in engineering. Besides practical, thermocouple also has very wide range of sizes and applications. Nevertheless, particular study on the thermocouple performance especially in terms of imperfections due to mechanical defect were never conducted. This is important since mechanical surface defect i.e. wear and crack can be frequently happened in practice. This study, therefore, investigate the effect of mechanical surface defects on the thermocouple performance during calibration. Eight samples of thermocouple with various wear and crack have been fabricated and tested in a calibration apparatus following NIST 250-25 standard with temperature variation from 75ºC, 100ºC, 125ºC and 150ºC. It is found that each type of mechanical surface imperfections (wear& crack) on the probes gives different effect to the performance with a different pattern as well. The uniformity of the heat to the sensor surface plays as the major cause to the performance.